Are Islamic Banks Immunefrom Global Financial Crisis: Evidences from 16-Cross-Country Islamic Banks (Global Journal of Management and Business Research, 2013)
This paper empirically investigates whether the cross-country Islamic banks' financial performances are immune by the global financial crisis (GFC). Banks' financial performancesthe pre GFC and the GFC period-are measured by return on assets (ROA). The comparison of mean and the median return on return on asset (ROA) show that Islamic banks' ROA prior to GFC were 0.031 and 0.012 respectively and they were 0.01 and 0.12 respectively during the GFC. The significance of the parametric mean test,-t-test, and non-parametric median test,-Kruska-Wallis, and Mann-Whitney demonstrates a significant difference between the mean and the median performance of Islamic bank during the pre GFC and the GFC periods. This difference suggests that Islamic banks' financial performance is not immune from the GFC.
Keywords: islamic bank; financial performance; global financial crisis